Niveles de eficiencia administrativa en el Servicio de integración laboral de los Ríos - Villacres Alvarez, Andres Eloy (2018)
The present case study refers to an investigation that was carried out in the Labor Integration Service for people with SIL disability, for which different types of problems that arise in said organization were analyzed. This unit is located in the city of Babahoyo, Province of Los Ríos, is directed to the user's guidance to locate a job and / or to improve the work profile through a relevant training of the person with disabilities that is in search of job offers. The person with disabilities, a user of the SIL Service, will be part of a process of improvement and labor inclusion.